Characteristic Alterations of Network in Patients With Intraoperative Stimulation-Induced Seizures During Awake Craniotomy - Fang, Shengyu; Zhou, Chunyao; Wang, Lei; Fan, Xing; Wang, Yinyan; Zhang, Zhong; Jiang, Tao (Frontiers in Neurology, 2021)
Background The use of electrocorticography to avoid intraoperative stimulation-induced seizure (ISS) during awake craniotomy is controversial. Although a standard direct cortical stimulating (DCS) protocol is used to identify the eloquent cortices and subcortical structures, ISS still occurs. Epilepsy is related to alterations in brain networks. In this study, we investigated specific alterations in brain networks in patients with ISS. Methods Twenty-seven patients with glioma were enrolled and classified into the ISS and non-ISS groups based on history of ISS occurrence. A standard DCS protocol was used during awake craniotomy without electrocorticography supervision. Graph theoretical measurement was used to analyze resting-state functional magnetic resonance imaging data to quantitatively reveal alterations in the functional networks. Results In the sensorimotor networks, the glioma significantly decreased the functional connectivity (FC) of four edges in the ISS group, which were conversely increased in the non-ISS group after multiple corrections (p < 0.001, threshold of p value = 0.002). Regarding the topological properties, the sensorimotor network of all participants was classified as a small-world network. Glioma significantly increased global efficiency, nodal efficiency, and the sigma value and decreased the shortest path length in the ISS group compared with non-ISS group (p < 0.05). Conclusions The specific alterations indicating patient susceptibility to ISS during DCS were increased global and nodal efficiency and decreased shortest path length and FC induced by gliomas. If the patient has these specific alterations, electrocorticography is recommended to monitor after-discharge current during DCS to avoid ISS.